PULIRAN: A CRITICAL ASSESSMENT OF THE SUSTAINABILITY OF THE LAGUNA DE BAY AND ITS IMPLICATIONS TO THE BIO-REGION - Calizo, Sylwyn C. (PEOPLE: International Journal of Social Sciences, 2016)
Amidst the global shift towards sustainability, critically assessing the Laguna de Bay’s sustainability as a bio-region is imperative. Its role as a large natural ecosystem offers an opportunity to observe the sustainable framework phenomenon. The human-environment interaction is rich, and the ecological degradation of the lake can be linked with nearby lakeshore towns. With a holistic framework composed of the four fundamental elements of sustainability, that is, institution, society, ecology, and economy, the sustainability of the Laguna de Bay can be assessed. In doing this, microcosmic representatives through the barangays of Limbon-Limbon and Ithan have been taken. The data framework is composed of both quantitative and qualitative data triangulated with secondary data to produce a strong data output. Regression analysis, indexing, and plotting in the Cartesian plane are the quantitative data analyses used whilst a transcendental phenomenological approach has been applied to the qualitative data for understanding the human experience. Findings have shown that the Laguna de Bay has a very weak sustainability index (i.e., 0.0001) and a bias towards an anthropocentric worldview. Additionally, qualitative analysis has shown that the community has a strong regard for cultural capital whilst falling in the rest of the components. Transcendentally, a deep longing for the past with apparent regret and hopeful involvement depicts the sustainability phenomena. Puliran holds deep possibilities for social change as it estimates the phenomenon of sustainability, and quantitatively leads to how a weak sustainable framework can be optimized and balanced for a strong sustainable framework.